Low-Latency VLC System with Fresnel Receiver for I2V ITS Applications - Tassadaq Nawaz; Marco Seminara; Stefano Caputo; Lorenzo Mucchi; Jacopo Catani (Journal of Sensor and Actuator Networks, 2020)
This work presents a characterization of a low-cost, low-latency Visible Light Communication (VLC) prototype for infrastructure-to-vehicle (I2V) communication for future Intelligent Transportation Systems (ITS). The system consists of a regular traffic light as a transmitter (the red light is modulated with the information), and a photodetector as a receiver. The latter is equipped with low-cost Fresnel lenses as condensers, namely, 1 <semantics> ′ </semantics> <semantics> ′ </semantics> Fresnel and 2 <semantics> ′ </semantics> <semantics> ′ </semantics> Fresnel, to increase the optical gain of the system at the receiver. The system is capable of Active Decode and Relay (ADR) of information to further incoming units. The experimental characterization of amplitude and Packet Error Rate (PER) for the proposed system has been performed for distances up to 50 m. The results show that by incorporating the 2 <semantics> ′ </semantics> <semantics> ′ </semantics> Fresnel lens in the photodetector, an error free ( <semantics> PER ≤ 10 − 5 </semantics> ) I2V communication is established up to 50 m. Furthermore, the prototype can be used for both broadcast and beaconing transmission modes. This low-cost VLC-based system could offer sub-millisecond latency in the full ADR process for distances up to 36 m, which makes it suitable for integration in Cellular-V2X (C-V2X) and 5G platforms.